Association of CYP2C19 genotypes with postoperative atrial fibrillation after coronary artery bypass surgery - Qin Jiang; Keli Huang; Lizhu Han; Hong Kong; Zhenglin Yang; Shengshou Hu (Wiley, 2024)
Abstract This cohort study aims to assess the connection between cytochrome P450 family 2 subfamily C member 19 (CYP2C19) genotyping, platelet aggregability following oral clopidogrel administration, and the occurrence of postoperative atrial fibrillation (POAF) after off‐pump coronary artery bypass graft (CABG) surgery. From May 2017 to November 2022, a total of 258 patients undergoing elective first‐time CABG surgery, receiving 100 mg/day oral aspirin and 75 mg/day oral clopidogrel postoperatively, was included for analysis. These patients were categorized based on CYP2C19 genotyping. Platelet aggregability was assessed serially using multiple‐electrode aggregometry before CABG, 1 and 5 days after the procedure, and before discharge. The incidences of POAF were compared using the log‐rank test for cumulative risk. CYP2C19 genotyping led to categorization into CYP2C19*1*1 (WT group, n = 123) and CYP2C19*2 or *3 (LOF group, n = 135). Baseline characteristics and operative data showed no significant differences between the two groups. The incidence of POAF after CABG was 42.2% in the LOF group, contrasting with 22.8% in the WT group (hazard risk [HR]: 2.061; 95% confidence interval [CI]: 1.347, 3.153; p = 0.0013). Adenosine diphosphate‐stimulated platelet aggregation was notably higher in the LOF group compared to the WT group 5 days after CABG (30.4% ± 6.5% vs. 17.9% ± 4.1%, p < 0.001), remaining a similar higher level at hospital discharge (25.6% ± 6.1% vs. 12.2% ± 3.5%, p < 0.001). The presence of CYP2C19 LOF was linked to a higher incidence of POAF and relatively elevated platelet aggregation after CABG surgery under the same oral clopidogrel regimen.